2000
DOI: 10.1046/j.1365-2796.2000.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Does dialysis therapy improve autonomic and peripheral nervous system abnormalities in chronic uraemia?

Abstract: Abstract. Laaksonen S, Voipio-Pulkki L-M, Erkinjuntti M, Asola M, Falck B (University Hospital, Turku, Finland). Does dialysis therapy improve autonomic and peripheral nervous system abnormalities in chronic uraemia? J Intern Med 2000; 248: 21±26.Objectives. Autonomic nervous system (ANS) dysfunction and peripheral neuropathy occur in patients with chronic renal insufficiency. Adequate renal replacement therapy should prevent development or correct these abnormalities. Design and subjects. We studied retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 14 publications
4
34
1
1
Order By: Relevance
“…Uremia in chronic renal failure may increase the risk of infection (11), polyneuropathy (12), autonomic dysfunction (13), and peripheral vascular disease (14), all of which can be involved in the pathogenesis of LEA. Hemodialysis inadequacy has been found to be associated with mortality due to coronary artery disease, other cardiac disease, cerebrovascular disease, and infection and with allcause mortality (15).…”
Section: Discussionmentioning
confidence: 99%
“…Uremia in chronic renal failure may increase the risk of infection (11), polyneuropathy (12), autonomic dysfunction (13), and peripheral vascular disease (14), all of which can be involved in the pathogenesis of LEA. Hemodialysis inadequacy has been found to be associated with mortality due to coronary artery disease, other cardiac disease, cerebrovascular disease, and infection and with allcause mortality (15).…”
Section: Discussionmentioning
confidence: 99%
“…Systolic blood pressure declined more than 2 mmHg at 6 and 12 months, and diastolic blood pressure declined 16.6 ± 5.4 mmHg and 6.6 ± 6.4 mmHg in parallel (25). In other studies in HD patients, HD sessions were noted to improve HRV (30,31), an effect that can be interpreted as a consequence of better removal of uremic toxins, as well as better control of extracellular volume.…”
Section: Discussionmentioning
confidence: 70%
“…However, the study of ANF in ESRD especially in PD patients is still limited. Laaksonen et al [29] showed that the adequacy of dialysis may be a predictor of improvement of cardiac ANF and Dursun et al [30] suggested that dialysis can cause a significant improvement in ANF in CAPD patients. However, the relationship between HRV and RRF which is crucial for PD has not been elucidated by the previous studies.…”
Section: Discussionmentioning
confidence: 99%